2004
DOI: 10.1007/s00122-004-1712-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of a soybean bacterial artificial chromosome library and use of multiple complementary libraries for genome physical mapping

Abstract: Two plant-transformation-competent large-insert binary clone bacterial artificial chromosome (hereafter BIBAC) libraries were previously constructed for soybean cv. Forrest, using BamHI or HindIII. However, they are not well suited for clone-based genomic sequencing due to their larger ratio of vector to insert size (27.6 kbp:125 kbp). Therefore, we developed a larger-insert bacterial artificial chromosome (BAC) library for the genotype in a smaller vector (pECBAC1), using EcoRI. The BAC library contains 38,40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…6) range from < 50 kb to 260 kb. Despite the double selection, there is quite a large number of clones shorter than 50 kb, which correlates with the results obtained by other authors [21,[25][26]. The average length of clones in the library is 135 kb.…”
Section: The Characteristics Of the Bac Library And Isolation Of Clonsupporting
confidence: 89%
“…6) range from < 50 kb to 260 kb. Despite the double selection, there is quite a large number of clones shorter than 50 kb, which correlates with the results obtained by other authors [21,[25][26]. The average length of clones in the library is 135 kb.…”
Section: The Characteristics Of the Bac Library And Isolation Of Clonsupporting
confidence: 89%
“…In the case of chickpea, a BIBAC library consisting of 23,780 clones, with an average insert size of 100 kb and covering about 3.8X genomes of chickpea was developed [93]. However, multi-enzyme BAC libraries with higher genome coverage are required for comprehensive genome research [94][95][96]. Subsequently, Lichtenzveig et al, [54] developed a BAC and BIBAC library in chickpea from the Hadas genotype; digested with HindIII and BamHI enzymes, respectively.…”
Section: Physical Mappingmentioning
confidence: 99%
“…The construction of BAC libraries and the physical map helped put the fragmented genome sequence of Forrest together (Shultz et al, 2006). Although the Forrest cultivar library and the BAC libraries for the Asgrow 3244 and the Williams 82 susceptible cultivars were available, complete BAC libraries did not exist for either cultivar (Wu et al, 2004). Wu et al (2004) reported a complete physical map from three BAC libraries derived from the Forrest cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Forrest cultivar library and the BAC libraries for the Asgrow 3244 and the Williams 82 susceptible cultivars were available, complete BAC libraries did not exist for either cultivar (Wu et al, 2004). Wu et al (2004) reported a complete physical map from three BAC libraries derived from the Forrest cultivar. As the BAC libraries created complement each other, they expanded the number of clones used soybean genome analysis.…”
Section: Introductionmentioning
confidence: 99%